Correction to: Ficus sycomorus extract reversed behavioral impairment and brain oxidative stress induced by unpredictable chronic mild stress in rats - Harquin Simplice Foyet; Serge Tchinda Deffo; Pascaline Koagne Yewo; Iulia Antioch; Stéphane Zingue; Emmanuel Acha Asongalem; Pierre Kamtchouing; Alin Ciobica (BMC, 2017)
Correction After the publication of this article [1] it came to our attention that Harquin Simplice Foyet was incorrectly included as Harquin Simplice Harquin Foyet. The corrected name is included in the author list. The original article was updated.